1996
DOI: 10.1681/asn.v75653
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II modulates glomerular capillary permselectivity in rat isolated perfused kidney.

Abstract: Studies in experimental animals and humans have documented that inhibition of the renin-angiotensin system by angiotensin-converting enzyme inhibitors reduces urinary protein excretion rate and retards the development of renal injury. Here we sought to investigate whether angiotensin II (All) modified the size-selective properties to macromolecules of the glomerular capillary barrier in isolated perfused rat kidney preparation. Compared with basal values, continuous All infusion into the renal artery at the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…23 Angiotensin II might directly increase the glomerular barrier permeability to plasma macromolecules and proteinuria, independent of changes in systemic haemo dynamics and even intraglomerular capillary presssure. 24 Independent of BP control, intrarenal ACE activation is associated with accelerated progression of experimental chronic kidney disease 2,4 and enhanced proteinuria and faster loss of renal function in patients with diabetic and non-diabetic chronic nephropathies. 8,17 However, acti vation of the vitamin D receptor suppresses renin trans cription, 25 so vitamin D analogues might act as negative endocrine regulators of the RAS, in particular in com bination with ARBs, 11 as in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…23 Angiotensin II might directly increase the glomerular barrier permeability to plasma macromolecules and proteinuria, independent of changes in systemic haemo dynamics and even intraglomerular capillary presssure. 24 Independent of BP control, intrarenal ACE activation is associated with accelerated progression of experimental chronic kidney disease 2,4 and enhanced proteinuria and faster loss of renal function in patients with diabetic and non-diabetic chronic nephropathies. 8,17 However, acti vation of the vitamin D receptor suppresses renin trans cription, 25 so vitamin D analogues might act as negative endocrine regulators of the RAS, in particular in com bination with ARBs, 11 as in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact involvement in the pathophysiological mechanisms of renal and/or cardiovascular disease are not yet fully understood, it is known that high renin levels also have detrimental effects independent from Ang II, via binding (pro)renin receptor (Nguyen et al, 2004). Moreover, high concentrations of tissue Ang II induce pro-fibrotic, pro-inflammatory, and prohypertrophic effects that damage the kidney (Ames et al, 2019), influence urinary excretion of albumin (Clavant et al, 2003), and increased the fractional excretion of protein (Lapinski et al, 1996). Despite the involvement of alternate pathways involving enzymes such as chymase in the generation of Ang II, the predominant enzymes involved in Ang II generation include renin and ACE.…”
Section: Discussionmentioning
confidence: 99%
“…Lapinski et al 15 explained that the angiotensin II via increase in glomerular capillary pressure. They suggested that a vicious cycle is established in which the changes in renal hemodynamics due to the loss of nephrons lead to proteinuria which is then followed by the loss of more nephrons.…”
Section: Effect On Urinary Proteinsmentioning
confidence: 99%